Two-dimensional echocardiographic evaluation in liver cirrhosis patients in prediction of cirrhotic cardiomyopathy - Dinić-Radović, Violeta A; Nagorni, Aleksandar V; Radović, Milan M; Apostolović, Svetlana; Bjelaković, Goran B; Radovanović-Dinić, Biljana; Tešić-Rajković, Snžana (Vojnosanitetski pregled, 2017)
Background/Aim. Cirrhotic cardiomyopathy (CCM) is a clinical syndrome in liver cirrhosis (LC) patients, which is characterized by the abnormal cardiovascular (CV) response to physiologic, pathologic, or pharmacologic stress provocation, but normal to increased cardiac output and contractility at rest. The aim of the study was to identify the structural and functional myocardial changes in the prediction of CCM in patients with LC of various origins in advanced stages. Methods. The research was performed as a prospective, nest case-control study, on carefully selected 40 patients in the advanced stage of LC and negative personal medical history on previous CV disease and 40 healthy subjects as the control, from January 2012–December 2014. Echocardiographic parameters significant for prediction of the development and/or presence of CCM were determined by trans-thoracic two-dimensional Doppler echocardiography imaging. Results. Most of the LC patients were alcoholic (80%), dominantly in Child-Pough C stage of the disease (70%). The average value of QT interval in the LC patients was significantly higher (0.44 ± 0.03 ms vs 0.42 ± 0.01 ms; p < 0.001), as well as brain natriuretic peptide (BNP) serum level (284.61 ± 181.44 ng/L vs 69.41 ± 31.08 ng/L; p < 0.001) compared to those in the healthy subjects. A significant association with serum BNP level in LC patients was shown with left atrial diameter (p = 0.031), left ventricular ejection fraction (p = 0.014), pulmonary artery systolic pressure (PASP) (p = 0.000) and the presence of tricuspid valve regurgitation of 2+ (p = 0.000), affecting its change of 41.6%. Conclusion. The obtained results suggest that LC patients have significant echocardiographic signs of myocardial dysfunction, as well as the increased BNP serum level. Left atrial diameter, left ventricular ejection fraction, PASP and tricuspid valve regurgitation are valuable echocardiographic predictors of CCM.